“And He Gives Her a Bill of Divorcement” - Michaels, Marc (The review of rabbinic Judaism, 2024)
This essay explores the halakhic precedents that can be drawn upon concerning the need for, and possible form of, a גט geṭ (Jewish religious divorce) when one of the parties involved has undergone gender transition. Does a geṭ need to be written at all? If so, can the transgender partner (in the case considered, the former husband) give a geṭ? If so, what names should be used on the geṭ? Here we examine the reactions of the various Jewish denominational movements to this growing societal phenomenon and study how the denominational setting impacts the answers to those questions.